Ultra-processed food consumption and the risk of subclinical thyroid dysfunction: a prospective cohort study. Issue 6 (2nd March 2022) - Zhang, Juanjuan; Zhu, Fan; Cao, Zhixia; Rayamajhi, Sabina; Zhang, Qing; Liu, Li; Meng, Ge; Wu, Hongmei; Gu, Yeqing; Zhang, Shunming; Zhang, Tingjing; Wang, Xuena; et al.
Abstract : Prospective cohort studies linking ultra-processed foods (UPF) and subclinical thyroid dysfunction (SCTD) are limited, especially in Chinese adults. Abstract : Background : prospective cohort studies linking ultra-processed foods (UPF) and subclinical thyroid dysfunction (SCTD) are limited, especially in Chinese adults. Objective : we designed a large-scale cohort study to examine whether UPF consumption is a risk factor for SCTD in adults. Methods : this prospective cohort study investigated 8732 participants (mean age: 44.7 ± 10.7 years; 53.3% men). UPF consumption was measured at the baseline using a validated food frequency questionnaire and classified according to the NOVA classification system. SCTD was characterized by abnormal serum thyroid-stimulating hormone levels and normal free thyroxine. Cox proportional hazards regression models were used to examine the association of UPF consumption with the risk of various types of SCTD. Results : during the follow-up period, the incidence rate of subclinical hypothyroidism was 8.3/1000 person-years and that of subclinical hyperthyroidism was 7.0/1000 person-years. After adjusting the potential confounding factors, the multivariable hazard ratios (HRs) (95% confidence intervals) across increasing tertiles of energy-adjusted UPF consumption for subclinical hypothyroidism were 1.00 (reference), 0.82 (0.57, 1.18) and 0.87 (0.60, 1.27) ( P for trend = 0.47) and for subclinical hyperthyroidism were 1.00 (reference), 1.09 (0.71, 1.68) and 1.69 (1.12, 2.56) ( P for trend = 0.01). Per one standard deviation (58.0 g per 1000 kcal per day) increase in ultra-processed food consumption a 14% increase in risk of subclinical hyperthyroidism was observed (HR = 1.14; 95% CI: 1.00, 1.30; P = 0.04). Further sensitivity analysis showed that the fully adjusted HRs (95% CIs) of subclinical hyperthyroidism across tertiles of the proportion of UPF in weight for subclinical hyperthyroidism were 1.00 (reference), 1.06 (0.69, 1.63) and 1.63 (1.09, 2.46) ( P for trend = 0.01). Conclusions : this population-based prospective cohort study has firstly demonstrated that higher UPF consumption was associated with higher risk of subclinical hyperthyroidism in adults. The UMIN clinical trial registry number is UMIN000027174 (; https://upload.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000031137 ).